Estudo pós-colheita de goiabas ‘paluma’ (Psidium guajava L.) revestidas com películas biodegradáveis com e sem associação de óleo essencial (Research, Society and Development, 2020)
This work aimed to evaluate the efficiency of biodegradable films, made from the cassava starch associated or not with essential oil of the orange peel 'Pêra' (OECL) (Citrus sinenses L.) in the shelf life in guavas "Palumas" (Psidium guajava L.). For that, the quality of the OECL applied in the production of biodegradable film based on cassava starch was extracted and evaluated. The guavas used were submitted to the treatments: Control, without coating = T1, with coating of 2% cassava starch (FM) without association with essential oil of orange peel = T2 and with coating of FM at 2% + association of oil essential orange peel = T3. The study was carried out in 2 lots, totaling 42 analyzed fruits, arranged in an air-conditioned chamber with a temperature of 25 ± 2 ºC and RH of 90 ± 2%, remaining for a period of up to 12 days, with physical-chemical pH analyzes , total titratable acidity (TTA), total soluble solids (TSS), total soluble solids and total titratable acidity (ratio), vitamin C, fruit firmness, weight loss, pulp color, skin color and microbiological analysis of molds and yeasts performed at times 0, 2, 4, 6, 8, 10 and 12 days, on a fruit corresponding to each treatment. The films did not show improvement in the evaluated parameters, in comparison with the guavas without coating (T1). Thus, biodegradable films made in similar conditions aren’t recommended for improving shelf life in “Palumas” guavas (Psidium guajava L.).